TikTok marketing and influencer review on azarine sunscreen purchase intention : the mediation of brand image - Suwandi, Della; Pebrianti, Wenny; Listiana, Erna; Ramadania, Ramadania; Syahbandi, Syahbandi (Institute of Computer Science (IOCS), 2023)
This research aims to test how TikTok social media marketing and influencer reviews can influence consumer interest in making purchases of azarine Sunscreen products with brand image as a mediating variable. Data was collected using the Google Form online questionnaire method aimed at 252 respondents using a purposive sampling technique with a quantitative approach. TikTok users who have seen advertisements for Azarine products and have seen influencer Tasya Farasya reviewing products Sunscreen Azarine was used as the population for this study. Data were analyzed through structural equation modeling (SEM) with AMOS 24 tool to analyze and evaluate measurement models and structural models of the research constructs being built. The research found that social media marketing and influencer reviews on purchase intention had a significant and positive influence. Brand image on purchase intention significantly and positively influences social media marketing and influencer reviews on consumer purchase intention